The Use of the 'Job to Be Done' methodology to identify value co-creation opportunities in the context of the Service Dominant Logic - Áurea Helena Puga Ribeiro; Plínio Rafael Reis Monteiro; Laura Luttembarck (BBR: Brazilian Business Review)
Organizations that operate in B2B contexts adopt value-creation strategies aimed at customer loyalty. Based on the concepts of the Service Dominant Logic (SDL), the study proposes the use of the Job to Be Done (JTBD) technique as a method to support the implementation of SDL concepts, applying the Outcome Driven Innovation (ODI) approach. Results of a survey carried out with 450 customers of a chemical company pointed out that the jobs revealed by the customers, once solved, actually result in better performance, thus contributing to confirm the adequacy of the technique for the purpose of identifying and prioritizing customers with greater potential for co-creation. The study also evaluates the variable ‘professional management’ as a moderator of this relationship and confirms that the solution of the jobs considered relevant by the customers, in a context of professional management, enhances co-created value.